Energy storage performance improvement of phase change materials-based triplex-tube heat exchanger (TTHX) using liquid–solid interface-informed fin configurations. (1st March 2023) - Palmer, Ben; Arshad, Adeel; Yang, Yan; Wen, Chuang
Highlights: Fluid-solid interface-informed fin configuration to enhance phase change material performance. Natural convection of melting process of phase change materials is considered in the simulations. Efficient melting performance is achieved in tubular thermal energy storage systems. Charging performance is improved by 57.4 % using fluid-solid interface-informed fin configurations. Abstract: The future of power generation is predicted to be greener with greater uptake in renewable energy which will be more intermittent and make matching demand harder. Latent thermal energy storage using phase change materials (PCMs) could provide a solution to that problem. PCMs can store large amounts of energy in small volumes, however, the main issue is the low conductivity of PCMs, which limits the rate that energy can be stored due to the slow melting and solidification processes. In the present study, we design and optimise a flow structure-informed fin configuration for triplex-tube heat exchangers (TTHXs) that accelerates the PCM melting process to allow for faster energy storage rates. The computational fluid dynamics modelling is developed to evaluate different TTHX geometries and find the most efficient fin geometries. The results show that an optimal fin geometry can provide a 57.4 % reduction in melting time, which demonstrates that fins offer a very effective way of reducing the melting times of PCMs without taking up much volume. We also found that fins in the lower half of the PCM are more effective in reducing total melt time than fins in the upper half. It is revealed that curved fins offer better performance when compared to similar straight fins. Lastly, it is observed that horizontal or angled surfaces allow for more natural convection in TTHX. The findings can be used to inform future studies on energy storage performance improvement of PCMs.